Increasing Vocabulary of Pupils Using Didactic Games (Eurasian Journal of Learning and Academic Teaching, 2022)
The article reflects on the use of didactic games, plot games, role-playing games, businessgames, dramatic games and innovative forms of education with an innovative characterin order to strengthen the educational and cognitive activity of students in modernconditions, improve the quality and effectiveness of training